2016
DOI: 10.1159/000448750
|View full text |Cite
|
Sign up to set email alerts
|

Ponatinib Induces a Persistent Molecular Response and Graft-versus-Host Disease/Graft-versus-Leukemia Effect in a Patient with Philadelphia-Positive Acute Lymphoblastic Leukemia with a T315I Mutation following Early Relapse after Allogeneic Transplant

Abstract: We describe the case of a patient with a Philadelphia-positive (Ph+) acute lymphoblastic leukemia (ALL) treated with dasatinib plus steroids as the first-line therapy who achieved a molecular complete remission and then underwent a matched, unrelated donor allogeneic transplant. Five months after the transplant, he experienced a disease relapse with an T315I mutation, which was resistant to salvage Key WordsAcute lymphoblastic leukemia · Philadelphia chromosome · Allogeneic transplant · Ponatinib · T315I mutat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 15 publications
1
6
1
Order By: Relevance
“…Three clinical trials have confirmed the efficacy of ponatinib in the relapsed and front-line setting in Ph+ ALL patients, even in the presence of the T315I mutation. These data support the characterization of ponatinib as a pan-BCR/ABL inhibitor and therefore supports its use in Ph+ ALL patients resistant or intolerant to dasatinib and for whom subsequent treatment with imatinib is not clinically appropriate, or in patients harboring the T315I mutation [8,9,10]. …”
Section: Introductionsupporting
confidence: 70%
See 1 more Smart Citation
“…Three clinical trials have confirmed the efficacy of ponatinib in the relapsed and front-line setting in Ph+ ALL patients, even in the presence of the T315I mutation. These data support the characterization of ponatinib as a pan-BCR/ABL inhibitor and therefore supports its use in Ph+ ALL patients resistant or intolerant to dasatinib and for whom subsequent treatment with imatinib is not clinically appropriate, or in patients harboring the T315I mutation [8,9,10]. …”
Section: Introductionsupporting
confidence: 70%
“…Recently, a similar case report described a patient with Ph+ ALL with the acquisition of T315I mutation who was treated with ponatinib at relapse after an allogeneic transplant. This patient also experienced a skin GVHD, suggesting that the efficacy of ponatinib could be related to its ability to promote an indirect GVL effect [10]. This finding reinforces the use of immunotherapy in the treatment of onco-hematological diseases [13].…”
Section: Discussionmentioning
confidence: 58%
“…Although both patients achieved deep molecular responses, they also developed cutaneous GVHD which required medication discontinuation in the patient with CML 47. Skin GVHD following initiation of ponatinib for posttransplant relapses has also been described in other case reports, suggesting a potential role of ponatinib to enhance the graft-versus-leukemia effect 48,49. Overall, 43 patients have received ponatinib for posttransplant relapses in the early phase clinical trials; however, their clinical outcomes and side-effect profile have not been reported separately 15,16…”
Section: Patient Selectionmentioning
confidence: 85%
“…New drugs, such as monoclonal antibodies or third generation TKIs, offer new possibilities for treatment of these patients. Few clinical experiences published so far evaluate the use of these drugs in the “posttransplant” setting [19, 20]. We described the case of a patient affected by Ph’+ ALL following early relapse after a second HSCT, who was treated with a combination of IO, DLI, and ponatinib.…”
Section: Discussionmentioning
confidence: 99%